Efficacy and safety of a new selective laser device to create anterior capsulotomies in cataract patients - Stodulka, Pavel; Packard, Richard; Mordaunt, David (Journal of cataract and refractive surgery, 2019)
PURPOSE: To compare the efficacy and safety of anterior capsulotomy creation with a new selective laser device (CAPSULaser) with those of manual capsulotomies. SETTING: GEMINI Eye Clinic, Zlin, Czech Republic. DESIGN: Prospective case series. METHODS: Patients were placed in cohorts based on age and cataract grade and randomly allocated to have laser capsulotomy or manual continuous curvilinear capsulorhexis (CCC). The anterior capsule was stained with microfiltered trypan blue 0.4%. The anterior capsulotomy was created with the laser device focused on the anterior capsule through a custom patient interface lens. Intraoperative video analysis with the use of an intraocular ruler and postoperative examinations were used to assess safety and efficacy (accuracy of capsulotomy size, circularity, centration). RESULTS: No intraoperative complications occurred in the laser group or the manual group. All capsulotomies in the laser group were free-floating with no tags or tears. The mean capsulotomy diameter was 5.03 mm overall (range 4.8 to 5.2 mm, laser group; 4.4 to 5.8 mm, manual group). In the laser group, all the capsulotomies were within 0.1 mm ± 0.1 (SD) of the target. The circularity accuracy was greater than 99.0% ± 1.0%; the mean centration of the capsulotomy in relation to the intraocular lens (IOL) was 0.1 ± 0.1 mm. All parameters were statistically significant (P < .01). The IOL-capsulotomy overlap was 360 degrees in all laser cases. CONCLUSIONS: Selective laser capsulotomy using a new proprietary trypan blue formulation was safe and effective in cataract surgery. The sizing, circularity, and centration of the laser capsulotomy were more accurate than those of the manual CCC, resulting in consistent 360-degree IOL coverage.
Keywords: senioři; Laser Therapy; Treatment Outcome; Pseudophakia; lidé; výsledek terapie; Anterior Capsule of the Lens; Lens Implantation, Intraocular; Middle Aged; mužské pohlaví; Capsulorhexis; Adult; Prospective Studies; Phacoemulsification; pseudofakie; trypanová modř; ženské pohlaví; capsulorhexis; prospektivní studie; zraková ostrost; Humans; Visual Acuity; fakoemulzifikace; lidé středního věku; barvicí látky; Trypan Blue; dospělí; Female; Aged; implantace nitrooční čočky; Coloring Agents; přední pouzdro oční čočky; katarakta; Cataract; laserová terapie; Male